1999
DOI: 10.1074/jbc.274.26.18613
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Herpes Simplex Type 1 Virus Origin-binding Protein (UL9 Protein) with Box I, the High Affinity Element of the Viral Origin of DNA Replication

Abstract: The herpes simplex type 1 (HSV-1) origin binding protein, the UL9 protein, exists in solution as a homodimer of 94-kDa monomers. It binds to Box I, the high affinity element of the HSV-1 origin, Ori s , as a dimer. The UL9 protein also binds the HSV-1 single strand DNA-binding protein, ICP8. Photocross-linking studies have shown that although the UL9 protein binds Box I as a dimer, only one of the two monomers contacts Box I. It is this form of the UL9 homodimer that upon interaction with ICP8, promotes the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
14
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 21 publications
4
14
0
Order By: Relevance
“…In Lee and Lehman (10,37), it was found that ICP8 would promote the unwinding of a short oriS-containing duplex if it either contained a ss tail or if the A͞T-rich spacer was unpaired. In He and Lehman (39), the 18-bp A͞T-rich spacer between boxes I and II was shown by hyperchromicity assays to be bound and opened by the addition of ICP8 and UL9 in an ATP-independent manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Lee and Lehman (10,37), it was found that ICP8 would promote the unwinding of a short oriS-containing duplex if it either contained a ss tail or if the A͞T-rich spacer was unpaired. In He and Lehman (39), the 18-bp A͞T-rich spacer between boxes I and II was shown by hyperchromicity assays to be bound and opened by the addition of ICP8 and UL9 in an ATP-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…When UL9 protein and ICP8 are incubated with linear, nonorigin-containing DNA possessing a 3Ј ss tail, UL9 is loaded onto the tails and, in the presence of ATP, translocates into the duplex segment unwinding it and providing a template for ICP8 binding (22,28). UL9 protein is a homodimer in solution, and several studies have shown that two dimers are bound to oriS containing all three binding boxes (9,10). Electron microscopy (EM) studies from this laboratory revealed a particle with a mass consistent with a double dimer assembled at oriS (29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the 37-kDa C-terminal DNA-binding domain has a dominant negative effect on viral replication, presumably because of its ability to occupy the origin nonproductively (16,17). Although the UL9 protein can bind to its recognition sequence as a homodimer, only one of the two monomers contacts the DNA (18). The dimerization of UL9 protein is mediated through the N-terminal part of the protein, presumably through a leucine zipper motif encompassing residues 150 -171 (19,20).…”
Section: Hsv-1 Gene Products Essential For Origin-specific Dnamentioning
confidence: 99%
“…It is a stable dimer that binds specifically and cooperatively to oriS (17). The C-terminal domain of OBP binds as a monomer to the recognition sequence GTTCGCAC referred to above as box I (18,19). Cooperative binding to boxes I and II is dependent on the N-terminal helicase domains of the protein (20).…”
mentioning
confidence: 99%